Urban microclimate at height: differences in air temperature vertical profile - Gapski, Natasha Hansen; Marinoski, Deivis Luis (ENCONTRO NACIONAL DE CONFORTO NO AMBIENTE CONSTRUÍDO, 2023)
Cities' morphologies determine the urban microclimate. The thermal conditions may differ according to the distance from the ground. For instance, air velocity and solar incidence tend to be higher as the height increases due to the decrease of obstacles to wind and radiation. This work discusses the gradient of vertical air temperatures in a high-rise building area. In winter and spring, measurements in the field at two heights on the same building occurred in the coastal Brazilian city of Balneário Camboriú. The air temperature was generally higher during the daytime at the highest point than the near ground one, especially in clear sky conditions, and lower during nighttime. As the sky view factor increases with height, the shading obstacles decrease, leading to generally higher solar access and a higher heat released through longwave radiation to the sky. Also, the studied area was modelled in ENVI-met and compared to field measurements. Simulation's results in the vertical profile showed the opposite behaviour than the field observations. Especially in high-density cities, understanding the vertical microclimate profile may guide the development of urban climate improvement strategies.